Metabolic reprogramming underlies metastatic potential in an obesity-responsive murine model of metastatic triple negative breast cancer - Ciara H. O’Flanagan (Nature Portfolio, 2017)
Triple negative breast cancer: Obesity and metabolism fuel disease spread Metabolic changes contribute to the metastatic potential of triple negative breast cancer (TNBC), a mouse study shows. Stephen Hursting and colleagues from the University of North Carolina at Chapel Hill, USA, established metastatic mouse TNBC cells driven by Wnt-1, a signaling protein that’s highly active in this aggressive subtype of breast cancer. In a lab dish, these cells showed signs of increased invasiveness; and when transplanted into mice, the cells readily formed tumors that metastasized to the lungs. Obese mice experienced more aggressive tumor growth and spread than normal-weight animals. Gene expression analyses revealed that TNBC cells with metastatic potential have an energetic leg-up over their non-metastatic counterparts in the face of obesity-induced metabolic changes, suggesting that targeting metabolic perturbations could help reduce the burden of metastatic TNBC, particularly for obese women.